ILMU ALLAH BERBANDING ILMU MANUSIA (Studi Deskriptif Ayat-ayat Alquran) - Muhamad Rezi (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2018)
The growth of sciences responses the growth of human brain. As mankind,human being gifted by God many bounties and special features more than other Hiscreatures. This growth make many changes and appearances in many aspects suchsocial, culture, and faith. Human always take many efforts to be better than the other oftheir species. Observations, writing, and practicing are the sign that human tend to bemove the brain. But the most important think should be hold is these all of this world isjust the great creatures by someone called Allah who has unlimited access to all of Hisproperties. But the creatures limited verily.